Distributed active RC sinusoidal oscillator control frequency by single pole amplifier - Pirajnanchai, V.; Janchitrapongvej, K.; Songthanapitak, N. (My University, 2004)
In this paper used an Active Uniformly Distributed RC lines (ŪRCs) circuit is application to sinusoidal oscillator. The frequency of oscillator can be controlled and adjustable by varying an single pole amplifier. The circuit incorporated an gain controller loop (ko) for amplitude stabilization with low distortion. The realization of simulation and experimental results are in reasona-bly good agreement with the theoretical , and very low harmonic distortion. This circuit can be suitable for the process fabricated LSI chip, and can be application in electronic communications system.